International responsibility of a state in the form of guarantees of non-repetition - Krivenkova, Maria V.; Kurdyukov, Gennady I. (Opción, 2019)
The study aims to investigate the invocation of international responsibility of a state in the form of guarantees of non-repetition in the international judicial body practice via comparative qualitative research methods. As a result, human right judicial bodies often go beyond the requirements of individual applicants, imposing additional requirements on the offender states for the provision of assurances and guarantees of non-repetition. In conclusion, the requirement to provide assurances and guarantees of non-repetition is used in exceptional cases when there is no confidence in the wrongdoing State